STRATEGI BERSAING DI DALAM INDUSTRI PERANCAH DAN BEKISTING SISTEM DENGAN MENGGUNAKAN METODE KANVAS MODEL BISNIS. STUDI KASUS : PT. BETON PERKASA WIJAKSANA - Argi Thaufani; Mohammad Hamsal (Journal Industrial Manufacturing, 2019)
Business competition, changes in consumer tastes, economic and social changes led to various challenges and opportunities faced by PT. Beton Perkasa Wijaksana. China-made bekisting presence in Indonesia with low prices become a challenge for PT. Beton Perkasa Wijaksana. Therefore, companies should determine and re-evaluate the competitive strategy of construction firms in the business world today.There are three objectives of this study. First, to determine the strength of the product PERI PT. Beton Perkasa Wijaksana in bekisting sales market share in Indonesia. Second, to determine what factors are the strength and the weaknesses of the company. Third, create business competition strategy for PT. Beton Perkasa Wijaksana.SWOT method focuses on the IFE and EFE measurements to determine the current condition of the company and where the current level PT. Beton Perkasa Wijaksana. Formulated a strategy which will be constructed by the method of Bussiness Model Canvas  which consists of nine pieces that reflect the company's box, where the BMC will look grouping of strategies that will be built in any part of it that exist in the company, which all the box will be connected to each other and have a relationship that will make strategies that can be applied. Keywords: Formwork, SWOT, IFE, EFE, Bussiness Model Canvas.